Revitalisasi Kearifan Lokal Aceh: Gagasan Islam dan Budaya dalam Menyelesaikan Konflik di Masyarakat - Riezal, Chaerol; Joebagio, Hermanu; Susanto, Susanto (Millati: Journal of Islamic Studies and Humanities, 2018)
This article answers the question of how the form of revitalization of local wisdom in Aceh culture as the capital to resolve conflicts in the community. The important thing that will support this article is how Islamic ideas and Acehnese culture combine into one formulated from within, at least strengthening traditional institutions as the basis for managing Aceh culture is an important discourse to measure indicators of the ongoing settlement of Islamic conflicts. The results indicate that the re-actualization of Aceh culture which had been submerged by the conflict and tsunami, has now been revived especially on the social bases that were lost and even blurred. When there was a conflict in the Acehnese community, the mechanism for resolving conflicts was carried out using the Acehnese cultural approach known as Diâet, Sayam, Suloh, Peusijuek and Peumat Jaroe, involving Aceh traditional institutions at the village level, such as the geuchik (village headman), teungku imum and traditional leaders. This local wisdom in the discourse of the Aceh Government has reached the implementation of policies by making regional regulations through qanun to revitalize Acehâs local wisdom by reviving some traditional institutions that have not been functioning.